Hemostatic and Fibrinolytic Abnormalities in Polycystic Ovary Syndrome - Targher, Giovanni; Zoppini, Giacomo; Bonora, Enzo; Moghetti, Paolo (Seminars in Thrombosis and Hemostasis, 2014)
Polycystic ovary syndrome (PCOS) is the most common form of anovulatory infertility, affecting up to 10% of women of reproductive age. This syndrome was first described in 1935 when American gynecologists Stein and Leventhal associated the presence of ovarian cysts with anovulation, obesity, and hirsutism. For many years, the effects of PCOS on coagulation and fibrinolysis have remained largely unexplored. This review summarizes current knowledge of the effects of PCOS on coagulation and fibrinolysis, and the putative mechanisms by which PCOS may contribute to the development of coagulation and fibrinolytic disorders. To date, there is relatively strong evidence suggesting that PCOS is associated with increased platelet aggregation and decreased plasma fibrinolytic activity. However, whether these hemostatic disorders are linked to the abnormal hormonal system in PCOS remains to be elucidated. Moreover, it should be emphasized that PCOS is a heterogeneous endocrine condition, and that the number of published studies is limited, the sample size of most of these studies is relatively small, and the selection of control subjects has not been always appropriate. Furthermore, well-designed studies on larger cohorts of carefully characterized PCOS patients are needed to provide more comprehensive information on this issue.
Keywords: hemostasis; polycystic ovary syndrome; thrombosis